Perancangan Media Sosialisasi Pola Asuh Anak Usia Pra Sekolah Dengan Media Utama Buku Ilustrasi - Khamadi; Yoga Kharisma Putra; Siti Hadiati Nugraini (AKSA: Jurnal Desain Komunikasi Visual, 2022)
In 2019, the Semarang City Social Service noted that there were still many children who did not receive proper care, which led to many cases of child problems in the city of Semarang. The problem factors of the child come from the family environment or the closest people, with children as victims or as perpetrators. This study aims to understand the issues regarding good parenting, as a basis for the design of educational media for pre-school age care for parents to care for their children well. The research method used is a qualitative research method, with methods of collecting data on field observations, literature studies, and interviews. The analytical method used is framing analysis. This research resulted in the design of an illustrated book that uses a booklet format with the title "Let's Become Great Parents!". The design of illustrated parenting books for pre-school age children from the social aspect is a solution to convey messages to the target audience in the city of Semarang.